2009
DOI: 10.1371/journal.pone.0004855
|View full text |Cite
|
Sign up to set email alerts
|

Cycle Inhibiting Factors (CIFs) Are a Growing Family of Functional Cyclomodulins Present in Invertebrate and Mammal Bacterial Pathogens

Abstract: The cycle inhibiting factor (Cif) produced by enteropathogenic and enterohemorrhagic Escherichia coli was the first cyclomodulin to be identified that is injected into host cells via the type III secretion machinery. Cif provokes cytopathic effects characterized by G1 and G2 cell cycle arrests, accumulation of the cyclin-dependent kinase inhibitors (CKIs) p21waf1/cip1 and p27kip1 and formation of actin stress fibres. The X-ray crystal structure of Cif revealed it to be a divergent member of a superfamily of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 47 publications
2
84
0
Order By: Relevance
“…Delivery of purified Cif proteins to HeLa cells (Cif Ec , Cif Bp , and Cif from Photorhabdus species) results in the accumulation of cell-cycle regulators, including p21 and p27, with this activity dependent on the active site cysteine (10). We have shown that WT Cif Yp also stabilizes p21, although the effect was weaker than that observed for Cif Ec (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Delivery of purified Cif proteins to HeLa cells (Cif Ec , Cif Bp , and Cif from Photorhabdus species) results in the accumulation of cell-cycle regulators, including p21 and p27, with this activity dependent on the active site cysteine (10). We have shown that WT Cif Yp also stabilizes p21, although the effect was weaker than that observed for Cif Ec (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…The cycle inhibiting factors (Cifs) comprise a family of T3SEs from animal pathogens and insect symbionts (7) that induce a cytopathic phenotype in host cells that includes cell-cycle arrest at the G 2 /M or G 1 /S transition (6,(8)(9)(10)(11)(12). It has been suggested that during the infection process, restriction of the host cell cycle might delay epithelial cell renewal and favor gut colonization (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The production and secretion of TEM fusion proteins were carried out as described previously (Charpentier & Oswald, 2004;Jubelin et al, 2009), except that bacteria were grown in D-MEM/HEPES (Invitrogen) with kanamycin at 37 uC for 6.5 h without adding IPTG. The data presented (normalized 450/520 nm emission ratio) are the mean values of the results from triplicate wells from three independent experiments and bars indicate standard error of the mean (SEM).…”
Section: Methodsmentioning
confidence: 99%
“…Cyclomodulins are genotoxic and/or modulate cell-cycle progression, proliferation, cell differentiation, and apoptosis (14)(15)(16)(17)(18)(19). In particular, colibactin, a hybrid polyketidenonribosomal peptide encoded by the pks genomic island, has genotoxic properties causing DNA double-strand breaks and chromosomal instability in human eukaryotic cells (18,19).…”
Section: Introductionmentioning
confidence: 99%